2021
DOI: 10.1108/ijcst-05-2020-0071
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing thermal resistance of a down sleeping bag

Abstract: PurposeTo have a better understanding of the heat transfer mechanisms in a sleeping bag and to investigate the factors influencing thermal resistance of a down sleeping bag.Design/methodology/approachThe mechanism of heat transfer in a sleeping bag was discussed in this paper. The thermal resistances of 24 samples were investigated. Besides, the relation between fill weight and thermal resistance, and that between the air permeability of fabric and thermal resistance, as well as that between down filling rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…There are three ways in which heat can be exchanged between the body and the environment: conduction (C), radiation (R) and convection (K). 18 The heat transfer process of clothes in water is a mixture of these three ways: heat passed by the fibers, heat radiated between the fibers and the water and heat transferred through the convection of the water. 19 Forced convection can be ignored because this study investigated thermal resistance under hydrostatic conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three ways in which heat can be exchanged between the body and the environment: conduction (C), radiation (R) and convection (K). 18 The heat transfer process of clothes in water is a mixture of these three ways: heat passed by the fibers, heat radiated between the fibers and the water and heat transferred through the convection of the water. 19 Forced convection can be ignored because this study investigated thermal resistance under hydrostatic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…When clothes become partially or completely wet, thermal insulation is an important physical characteristic to quantify their thermal comfort. 18 In the case of a victim falling into water, heat transfer occurs primarily in the part of the body in contact with the surface of the clothing. Since the clothes isolate direct heat transfer between the human body and the surrounding environment, the clothes act as an intermediate medium to prevent direct heat transfer from the surface of the human skin.…”
Section: Heat Conductionmentioning
confidence: 99%
“…Due to their complexity and requirement for larger sample sizes, machine learning methodologies are less suited for small-sample problems related to aerogel fabrics than the gray method. 53,54 Several studies [8][9][10]14,[16][17][18] have identified influencing factors of fabrics following repetitive washing based on previous knowledge, neglecting the variable contributions throughout the washing process. Real-world projects exhibit dynamic and changing correlations between independent and dependent variables, significantly impacting the accuracy of aerogel fabric thermal resistance predictions.…”
Section: Overall Findings and Potential Mechanismsmentioning
confidence: 99%
“…8,9 The relationships between fabric characteristics (e.g., weaving patterns, fabric mass, thickness, porosity, and hydrophobicity) and thermal resistance have been rigorously investigated over several decades. Prior studies have proposed various prediction models for the thermal properties of fabric products, such as statistical models, [8][9][10][11][12][13][14] artificial neural networks, [15][16][17][18] theoretical models of heat transfer, [19][20][21] and finite element models. [22][23][24] More recent studies 3,25,26 have examined the effects of recurrent washing on the thermal insulation performance of textiles, confirming a strong correlation between thermal resistance and parameters such as thickness, weight, air permeability, and porosity.…”
mentioning
confidence: 99%
See 1 more Smart Citation